Pengaruh Digital Marketing Terhadap Peningkatan Minat Beli Konsumen Pasca Kebijakan Pencabutan PPKM Pada UMKM Depok - Lembahyung, Balina; Handayani, Trisni (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2023)
This study aims to determine the effect of digital marketing on increasing consumer buying interest after the PPKM revocation policy at UMKM Jalan Baru Depok. The Incidental Sampling technique was used to collect samples in the study of 58 respondents based on people encountered. The method used is quantitative. In analysing the data using Simple Linear Regression to examine the results of the data obtained from the questionnaire, so that the research results are obtained, namely the existence of a positive and relevant influence on consumer buying interest of 57.5%, the rest is explained by other independent variables that are not included in the researcher's simple linear regression model